INDUKSI POLIPLOIDI DENGAN KOLKISIN PADA HIBRID F1 HASIL PERSILANGAN ANTAR SPECIES PADA TANAMAN PANILI ASAL CIAMIS - Damayanti, Fitri; Mariska, Ika (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Steem root disease caused by Fusarium oxysporum Schl. f. sp. Vanillae (Tucker) Gordon represent one internal issues of vanilla development (Vanilla planifolia Andrews). To obtain resistance clone to the disease, it can exploit resource of wild vanilla (V. albida B. L Syn) through crosses. Hybrids which were interspecific crossed generally were sterile. To overcome sterility problem of the hybrids, chromosome doubling was made by colchicine application. Explant used globular structure of proembryo from F1 seed result from a cross between wild vanilla of Ciamis as female parents and cultivated vanilla clone of Ciamis as male parent. Concentration level colchicine used were 0.00%, 0.05%, 0.10%, 0.20% and 0.25% with period of treatment of 3 and 6 days. After colchicine treatment embryo cultures were subcultured into new mwdium that was basal media Murashige-Skoog enriched with 2.5 mg/l BAP. Result of the experiment showed that colchicine treatment,globular structure were F1 embryo tending to inhibit early regeneration. The cultures showed variabilities from treatment of colchicin 0.20% during of 6 day and 0.25% for 3 days. Phenotypic performance of the chromosome doubled hybrids showing great variation in color and vigor of the culture. Tetraploid plant(2n=4x=64) was obtained from the colchicine treatment of 0.25% for 6 days. Chromosome addtion was followed by improvement of cell dimensions and organ magnification.